2014
DOI: 10.1186/s12931-014-0136-8
|View full text |Cite
|
Sign up to set email alerts
|

Defining adult asthma endotypes by clinical features and patterns of volatile organic compounds in exhaled air

Abstract: BackgroundSeveral classifications of adult asthma patients using cluster analyses based on clinical and demographic information has resulted in clinical phenotypic clusters that do not address molecular mechanisms. Volatile organic compounds (VOC) in exhaled air are released during inflammation in response to oxidative stress as a result of activated leukocytes. VOC profiles in exhaled air could distinguish between asthma patients and healthy subjects. In this study, we aimed to classify new asthma endotypes b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 28 publications
(37 reference statements)
0
33
0
2
Order By: Relevance
“…Specific analysis by GC-MS will then be necessary in order to unravel the identity of the combination of VOCs. Recent GC-MS studies have shown that asthma particularly features exhaled VOCs that are associated with lipid peroxidation and inflammatory phenotypes 21,57 , the distribution of which is likely to drive the distinction between the three clusters. Finally, given the nature of the project there is an inevitable influence of medication and smoking on top of endogenous biological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Specific analysis by GC-MS will then be necessary in order to unravel the identity of the combination of VOCs. Recent GC-MS studies have shown that asthma particularly features exhaled VOCs that are associated with lipid peroxidation and inflammatory phenotypes 21,57 , the distribution of which is likely to drive the distinction between the three clusters. Finally, given the nature of the project there is an inevitable influence of medication and smoking on top of endogenous biological mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Asthma is a heterogeneous and chronic respiratory illness. Due to its diversity, it is complicated to diagnose correctly . Over time, many investigators have searched for biomarkers, preferably noninvasive ones such as miRNAs detected in easily available biofluids …”
Section: Discussionmentioning
confidence: 99%
“…Several putative asthma-related VOCs (and other commonly reported VOCs such as C5 to C15 alkanes, acetone, isoprene, toluene, and internal standards) [22][23][24][25][26][27] were targeted for further assessment, based on predicted retention indices (using cubic spline interpolation within a retention index error threshold of ± 20) and mass fragments (extracted from Pubchem and NIST online chemical databases). The identity of compounds that met these search criteria were then confirmed by pre-processing chromatograms using AMDIS (version 2.72) and subsequently NIST14 library search.…”
Section: Data Pre-processing and Treatmentmentioning
confidence: 99%